(untitled) - Phillips, Sarah (Oxford, 1999)
The book provides practical ideas for introducing drama activities into the English class, including role play, mime, chants, puppets, and short plays. As well as develping speaking and pronunciation, drama helps children to develop self-confidence and express their imagination, personalities, and creativity.
Phương pháp dạy Tiếng Anh cho trẻ em
Keywords: English language,English language; Sudy and teaching,Textbooks for foreign speakers